A study on the impact of microfinance in alleviating the rural poverty in sri lanka (with special reference to hambantota district) - Krishanthi mallika, J. (university of Jaffna, 2014)
Sri Lanka has been successfully achieving the millennium development goal of poverty alleviation for last two decades showing a rapid reduction of poverty head count ratio from 26.1 percent to 8.9 percent from 1990/1991 to 2009/10. Hambantota District recorded the highest reduction in poverty head count ratio from 32.4 percent to 6.9 percent during the same period. Microfinance sector is dominating as a major poverty alleviation tool in Sri Lanka. The problem of this research is to what extent the microfinance contributes for poverty alleviation The data and information were collected from 240 samples the researcher has selected 150 treatment groups and 90 comparison groups randomly selected from three Divisional Secretariats representing all five selected microfinance institutions of Samurdhi, SANASA, Janashakthi bank, SEEDS and Rural banks. The structured questionnaire was the major research tool used in collecting primary quantitative data. Descriptive statistics and binary logistic regression models were used for the analysis tools. On the basis of analysis, author found that Poverty reduction of the area was highly contributed by microfinance institutions of SEEDS, Janashakthi Banking Societies, and Co-operative Rural Banks while Sanasa and Samurdhi Banks contributed less.
Keywords: Poverty; Poverty alleviation; Microfinance; Treatment groups; Comparison groups